Innovation as a Mechanism to Achieve Sustainable Development in Egypt - salah, Amany (The Arab Journal of Administration, 2022)
Innovation has become a locomotive of economic growth and sustainable development in developed and developing countries alike, where innovation is an innovative activity that contributes to product development, marketing methods and new or significantly improved organizational systems, and uses them to effect the desired societal impact, economic and social transformation, which has been called by many organizations “The International Organization”, headed by the “World Intellectual Property Organization” (WIPO), developed a systematic strategy to develop all areas of innovative activities that are applicable in all countries of the world. In Egypt, the Egypt Document for Sustainable Development “2030” stressed the harm The drive to drive the innovation, competitiveness and creativity of the engine being the primary engine of development, the study confirmed this relationship where the results of the study resulted in a common integration relationship between the innovation index (GII) and sustainable development in its various dimensions, the development dimension and the social dimension where R2 came 99.5%, 99.3%, respectively, at the level of Significance of 1%, and the environmental dimension requires more activation of innovation in the direction of improving the economic environment and reducing carbon emissions came 27.3% R2 using the (ARDL) Auto-Regressive Distributed Lag Model analysis.